2017
DOI: 10.1515/cipms-2017-0008
|View full text |Cite
|
Sign up to set email alerts
|

Marginal bone behavior around the dental implants with regard to the patient’s characteristics

Abstract: We analyzed the relationship between marginal bone loss around dental implants and selected personal characteristics of patients (gender, age and cigarette smoking) undergoing dental rehabilitation because of missing teeth. The study comprised 28 patients aged 37-66 years (11 men and 17 women) who had 240 implants inserted. The assessment of marginal bone loss in the examined patient cohort was made based on ortho-pantomographic X-ray images. For evaluation of the condition of the marginal bone around the impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
(17 reference statements)
1
0
0
Order By: Relevance
“…This study found no statistically significant differences between MBL in males and females in either smokers or non-smokers. These findings are in line with previous studies that showed neither sex [12,20] nor age had a significant effect on MBL in either smokers or non-smokers [12,21].…”
Section: Discussionsupporting
confidence: 93%
“…This study found no statistically significant differences between MBL in males and females in either smokers or non-smokers. These findings are in line with previous studies that showed neither sex [12,20] nor age had a significant effect on MBL in either smokers or non-smokers [12,21].…”
Section: Discussionsupporting
confidence: 93%